Effect of the Pelleting Process on Diet Formulations with Varying Levels of Crystalline Amino Acids and Reducing Sugars on Digestibility in Growing Pigs - K. M. Dunmire; D. A. Lopez; C. J. Fiehler; C. K. Jones; Y. Li; J. C. Woodworth; R. D. Goodband; M. D. Tokach; C. R. Stark; H. H. Stein; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of this study was to determine the effect of thermal processing on the digestibility of amino acids (AA) in diets with or without increased concentrations of free amino acids and reducing sugars (RS). To measure AA digestibility, a total of eight individually housed barrows (initially 69.2 ± 6.8 lb) that had a T-cannula installed in the distal ileum were allotted to a replicated 8 × 8 Latin square design with 8 diets and eight 7-d periods. Thus, each pig was fed each diet in one period and no pig received the same diet more than once. Each period lasted 7 days with the initial 5 days being the adaptation period, and ileal digesta was collected for 9 hours on d 6 and 7. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of crystalline AA concentration (low vs. high), reducing sugars (low vs. high), and diet form (mash vs. pellet). There was no feed form × crystalline AA inclusion × RS inclusion interaction for standardized ileal digestible (SID) AA. There was a feed form × RS interaction (P<0.026) for SID tryptophan. Feeding pelleted high RS diets resulted in decreased SID of tryptophan compared with mash high and low RS diets, and pelleted low RS diets. For the main effects of feed form, the SID of total AA, crude protein (CP), and indispensable AA increased (P<0.042) in pigs fed pelleted diets compared with those fed mash diets. For the main effects of crystalline AA inclusion, pigs fed low or high crystalline AA inclusion had similar SID of total AA and CP. Pigs fed high crystalline AA had increased (P = 0.007) SID of tryptophan compared with those fed low crystalline AA diets. The SID of lysine tended to increase (P = 0.076) in pigs fed high crystalline AA diets compared with those fed low crystalline AA inclusion diets. Pigs fed high crystalline AA had decreased (P = 0.050) SID histidine compared with those fed low crystalline AA diets. The SID of arginine and isoleucine tended to decrease (P<0.079), in pigs fed high crystalline AA. In pigs fed high crystalline AA, the SID of serine and glycine decreased (P<0.042) compared with those fed low crystalline AA. For the main effects of RS diets, pigs fed high RS diets had decreased (P<0.05) SID of total AA, CP, indispensable AA, alanine, aspartic acid, cysteine, glutamic acid, and serine. In conclusion, there was no evidence of interactions between diet types. Therefore, pelleting diets with increased concentration of crystalline AA or RS at the conditions reported herein did not reduce the AA digestibility. However, pelleting diets resulted in improved AA digestibility. Diets formulated with increased concentrations of crystalline AA had increased SID of tryptophan. Formulating diets with 20% DDGS and 15% bakery meal (high RS) resulted in decreased AA digestibility compared with the corn-soybean meal-based diets.
Keywords: crystalline amino acids; reducing sugars; Maillard reaction; pelleting; amino acid digestibility